2016
DOI: 10.1126/science.aad3456
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule inhibitor of sarcomere contractility suppresses hypertrophic cardiomyopathy in mice

Abstract: Hypertrophic cardiomyopathy (HCM) is an inherited disease of heart muscle that can be caused by mutations in sarcomere proteins. Clinical diagnosis depends on an abnormal thickening of the heart, but the earliest signs of disease are hyperdynamic contraction and impaired relaxation. Whereas some in vitro studies of power generation by mutant and wild-type sarcomere proteins are consistent with mutant sarcomeres exhibiting enhanced contractile power, others are not. We identified a small molecule, MYK-461, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
558
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 578 publications
(627 citation statements)
references
References 37 publications
36
558
2
3
Order By: Relevance
“…This result can be explained by the cMyBPC ablation‐induced displacement of XBs towards thin filaments and possibly reduced repression of XB movement, such that acto‐myosin interactions are increased, thereby resulting in enhanced XB‐mediated XB recruitment and force generation at submaximal Ca 2+ ‐activations 31, 47. Previous findings show that Myk461 inhibits myosin ATPase activity, decreases force generation, and prevents adverse cardiac remodeling in hypercontractile mouse hearts expressing HCM‐causing MHC missense mutations 21. It has been shown that myocardial samples isolated from HCM patients expressing cMyBPC mutations often display reduced total cMyBPC expression7, 25 and accelerated XB kinetics27; therefore, we sought to investigate the effects of Myk461 on the contractile function of myocardium lacking cMyBPC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result can be explained by the cMyBPC ablation‐induced displacement of XBs towards thin filaments and possibly reduced repression of XB movement, such that acto‐myosin interactions are increased, thereby resulting in enhanced XB‐mediated XB recruitment and force generation at submaximal Ca 2+ ‐activations 31, 47. Previous findings show that Myk461 inhibits myosin ATPase activity, decreases force generation, and prevents adverse cardiac remodeling in hypercontractile mouse hearts expressing HCM‐causing MHC missense mutations 21. It has been shown that myocardial samples isolated from HCM patients expressing cMyBPC mutations often display reduced total cMyBPC expression7, 25 and accelerated XB kinetics27; therefore, we sought to investigate the effects of Myk461 on the contractile function of myocardium lacking cMyBPC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the myosin modulator mavacamten (Myk461) has a potential role in attenuating cardiac hypercontractility caused by β‐MHC mutations by decreasing myosin ATPase activity and XB transitions to force‐generating states 21, 22. However, the effects of Myk461 on cardiac hypercontractility resulting from decreased cMyBPC expression have not been investigated until now.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations